Work Loyalty and Employee Retention from a Human Capital Perspective in the Faculty of Arts and Design at Sebelas Maret University - Dimas Yusuf Herlambang; Asri Laksmi Riani; M. Rudianto (Universitas Muhammadiyah Sorong, 2026)
This study aims to understand how employee work loyalty is formed and interpreted as a retention strategy from a human capital perspective at the Faculty of Arts and Design, Sebelas Maret University (FSRD UNS). This study uses a qualitative approach, specifically a transcendental phenomenological method, to explore employees' direct work experiences. Data were collected through in-depth interviews, participant observation, and documentation of four educational staff members selected via purposive sampling. Data analysis was carried out through the stages of organizing data, providing initial codes, developing themes, compiling textural and structural descriptions, and synthesizing the essence of the experience. The results show that employee loyalty is shaped by several interrelated factors: professional responsibility, emotional attachment, psychological comfort, competency development, family work culture, and perceptions of organizational justice. These factors create a supportive work environment and encourage employees to remain in the organization. This study concludes that work loyalty at FSRD UNS functions as a retention mechanism that develops organically through positive work experiences and social relationships within the organization, but has not been fully integrated into a structured human capital management strategy.